The Role Of Memorable Tourism Experience, Destination Image, And Perceived Value On Revisit Intention At Uluwatu Temple - Reza Previa Zahir; I Nyoman Sudiksa; Widi Hardini (LP2M IAIN Palopo, 2025)
This study investigates the influence of Memorable Tourism Experience (MTE) and Destination Image on Revisit Intention, with Perceived Value as a mediating variable, at Pura Luhur Uluwatu, Badung Regency, Bali. A mixed-method design combining quantitative and qualitative approaches was employed. The quantitative analysis was based on a survey of 315 domestic tourists who had previously visited Uluwatu, selected through accidental sampling, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The qualitative approach involved in-depth interviews with destination managers, tourism stakeholders, tour guides, and tourists to strengthen the interpretation of results. Findings reveal that both MTE and Destination Image significantly influence Perceived Value and directly affect Revisit Intention. Moreover, Perceived Value mediates these relationships. Theoretically, the results validate the Expectation–Disconfirmation Theory and Theory of Planned Behavior in explaining behavioral intention. Practically, the study suggests strategies to enhance experience quality, strengthen cultural image, and balance perceived benefits to sustain Uluwatu’s tourism competitiveness.